Pulsed-ozonolysis assisted oxidative treatment of forestry biomass for lignin fractionation. (October 2020) - Osorio-González, Carlos S.; Hegde, Krishnamoorthy; Brar, Satinder K.; Vezina, Pierre; Gilbert, Dave; Avalos-Ramírez, Antonio
Graphical abstract: Highlights: The thermochemical process is alternative method to improve delignification process. Sodium hydroxide is a suitable delignify agent. Softwood and hardwood sawdust are a suitable feedstock to produce monolignols. Pulsed ozonation is a promising method for improved monolignol production. Abstract: Lignocellulosic biomass has been used to produce biomolecules of industrial interest through thermochemical, biological, and chemical transformation. However, few works have been developed over lignin fractionation to obtain monolignols with commercial potentials, such as sinapyl, coniferyl, and p-coumaryl alcohols. This study is focused on developing a thermochemical method to delignify biomass. Additionally, an oxidative treatment with ozone was studied to increase the release of monolignol compounds. The results showed that with 30 sec of ozonation in liquid samples from softwood sawdust a total concentration of 368.50 ± 0.73 mg/kg of monolignols was released after microwave-assisted extraction (256.5 ± 0.51 mg/kg of sinapyl alcohol and 112 ± 0.22 mg/kg of coniferyl alcohol) and 629.20 ± 0.21 mg/kg was released after thermal treatment (453.70 ± 0.15 mg/kg of sinapyl alcohol and 175.5 ± 0.06 mg/kg of coniferyl alcohol). For p-coumaryl alcohol, 16.32 mg/kg was obtained only in hardwood samples. The results of the present study showed that ozonolysis improves monolignols release from forestry residues.